Analyzing the Soil Microbial Characteristics of IPoa alpigena/I Lindm. on Bird Island in Qinghai Lake Based on Metagenomics Analysis - Li, Lingling; Che, Zihan; Cao, Yanhong; Qi, Lulu; Chen, Kelong; Wang, Hengsheng (Water (Basel), 2023)
Poa alpigena Lindm. is a dominant forage grass that is widely distributed on the Qinghai-Tibetan Plateau and is often used in the restoration of degraded grasslands. Soil microorganisms are major players in the cycling of materials in terrestrial ecosystems. In this study, based on high-throughput sequencing, the rhizosphere and non-rhizosphere soils of Poa alpigena L. on Bird Island, Qinghai Lake, were used to investigate the effects of Poa alpigena L. on the composition and structure of soil microbial communities, and to establish associated soil microbial gene pools. Results revealed that microorganisms in the soil of Poa alpigena L. on Bird Island belonged to 62 phyla, 112 classes, 245 orders, 518 families, 1610 genera, and 5704 species. The dominant soil bacteria in rhizosphere and non-rhizosphere soils were Proteobacteria (49.62%, 47.13%) and Actinobacteria (30.31% and 31.67%), whereas the dominant fungi were Ascomycota (3.15% and 3.37%) and Basidiomycota (0.98% and 1.06%). Alpha diversity analysis revealed that the microbial richness and diversity in non-rhizosphere soil were significantly higher than those in rhizosphere soil, mainly influenced by soil water content and total nitrogen content. Furthermore, on the basis of LEfSe analysis, Alphaproteobacteria and Betaproteobacteria were identified as prominent differential taxa for rhizosphere and non-rhizosphere soils, respectively. The key differential metabolic pathways of rhizosphere soil microorganisms were those associated with the ATP-binding cassette (ABC) transporter, basal metabolism, and cytochrome P450 metabolism, whereas those of non-rhizosphere soil microorganisms included the gene expression-related pathways, methane metabolism, and pathway associated with degradation of aromatic compounds. These findings indicated that the rhizosphere soil of Poa alpigena L. is selective for microorganisms that play important roles in the oxidation of methane and regulation of the greenhouse effect on Bird Island, and that the soil environment on this island may be subject to contamination with aromatic compounds.